Al-Hakim's Pygmalion: Emulation and Creation - Ali Saleh Ahmed Al-Haidari; Mansour Mohammed Ali Faraj (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2018)
The use of classical myths is one of the ways that a lot of writers have adopted in composing their literary works. They are regarded as one of the main important sources that provide writers with many topics to explore, themes to depict, characters to portray, and motifs to analyze. However, some writers do not move beyond the events of the myth; they attempt to deal with it without violating its literary elements and events. On the other hand, some adapt its various elements to create a new work. In this paper, Al-Hakim's play Pygmalion is at the centre. It attempts to investigate, explore and analyze Al-Hakim's use of the myth of Pygmalion in creating his play Pygmalion. It also attempts to examine whether he adopts the same version of the Greek myth of Pygmalion or he violates its elements to create a new treatment of the myth.